In2O3 / MXene composite material, preparation method thereof and application of In2O3 / MXene composite material in detection of triethylamine
By coating the composite material of In2O3 and MXene, a specific nanoparticle structure is formed, which solves the problem of low conductivity when detecting triethylamine gas, and significantly improves gas sensitivity and detection performance, real-time detection and timely alarm of triethylamine gas is achieved.
Patent Information
- Application Number
- CN202510087767.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing In2O3-based sensors have low conductivity when detecting triethylamine gas, which limits its detection performance and is difficult to achieve real-time detection and timely alarm of triethylamine gas.
By covering the composite material composed of n-type semiconductor In2O3 and p-type semiconductor MXene, a rod-shaped nanoparticle structure is formed under a single-layer sheet-like wrap. There are fine and dense voids on the surface, providing rich active sites for the adhesion of oxygen, thereby improving gas-sensitive performance.
It significantly improves the gas sensitivity performance of In2O3, enhances the detection performance of triethylamine gas, achieves faster response and recovery time, and is suitable for real-time detection and timely alarm of triethylamine leakage.
Smart Images

Figure CN119780171A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of indium oxide-based composite materials, in particular to an In2O3 / MXene composite material and a preparation method thereof and triethylamine detection application. Background Art
[0002] In various chemical processes using triethylamine as industrial raw material, and in systems involving the production, storage and transportation of triethylamine, it is very important to achieve real-time detection and timely alarm of triethylamine leakage to provide support for the efficient application of energy safety technology.
[0003] Metal oxide semiconductor-based sensors have broad application prospects, especially In2O3, which has a good response to triethylamine gas. However, the low conductivity of In2O3 limits its detection performance. Composite with specific two-dimensional materials can greatly improve the detection performance of In2O3 and triethylamine gas. MXene is a p-type semiconductor. Single-layer MXene has the advantages of high conductivity similar to metal, high electron mobility, stable chemical properties, and high specific surface area. It has become one of the most promising materials in the fields of sensors, catalysis, energy storage, etc. Summary of the invention
[0004] The purpose of the invention is to provide an In2O3 / MXene composite material and a preparation method thereof and triethylamine detection application, which can effectively improve the gas-sensitive properties of indium oxide and enhance the detection performance of triethylamine gas.
[0005] Technical solution: The In2O3 / MXene composite material described in the present invention is a rod-shaped nanoparticle wrapped in a single layer of sheet-like material consisting of p-type semiconductor metal two-dimensional material MXene coated with n-type semiconductor In2O3, and there are gaps distributed on the surface of the rod-shaped nanoparticles to provide abundant active sites for the attachment of oxygen.
[0006] As a further limitation of the composite material of the present invention, the diameter of the rod-shaped nanoparticles is 30 nm to 70 nm.
[0007] The present invention also provides a method for preparing an In2O3 / MXene composite material, which is used to prepare the In2O3 / MXene composite material, and the specific steps are:
[0008] Step 1, preparing a single-layer MXene sheet;
[0009] Step 2, indium nitrate hydrate and MXene are mixed with NN-dimethylformamide respectively, and then stirred to obtain two mixed solutions, and then polyvinyl pyrrolidone is added to the two mixed solutions, and then stirred to mix;
[0010] Step 3, subjecting the stirred and mixed solution to electrospinning to obtain an In2O3 / MXene composite material precursor;
[0011] Step 4, annealing the In2O3 / MXene composite material precursor to obtain rod-shaped nanoparticles wrapped in a single layer of flakes, namely the In2O3 / MXene composite material.
[0012] As a further limitation of the preparation method of the present invention, in step 1, the specific steps for preparing a single-layer flaky MXene are:
[0013] Step 1.1, mixing hydrochloric acid and lithium fluoride in a polyethylene beaker, and then heating and stirring in a magnetic stirrer;
[0014] Step 1.2, adding aluminum titanium carbide for etching, and then performing centrifugation, ultrasound and freeze-drying treatment to obtain a single-layer flaky MXene.
[0015] As a further limitation of the preparation method of the present invention, in step 1.1, the mass ratio of hydrochloric acid to lithium fluoride is 1:10 to 1:20, the reaction time of heating and stirring in the magnetic stirrer is 5 to 15 minutes, the stirring speed range is 300 r / min to 400 r / min, and the oil bath temperature range is 38°C to 42°C.
[0016] As a further limiting scheme of the preparation method of the present invention, in step 1.2, when aluminum titanium carbide is added, the mass ratio of aluminum titanium carbide to hydrochloric acid is 1:20 to 1:30, and the etching reaction time ranges from 36 to 48 hours.
[0017] As a further limitation of the preparation method of the present invention, in step 2, the mass ratio of indium nitrate hydrate to MXene is in the range of 10:1 to 200:1, the mass ratio of indium nitrate hydrate to NN-dimethylformamide is 1:15, the mass ratio of MXene to NN-dimethylformamide is in the range of 1:150 to 1:3000, and the stirring and mixing time with NN-dimethylformamide is 5 to 15 minutes.
[0018] As a further limiting scheme of the preparation method of the present invention, in step 2, after polyvinyl pyrrolidone is added to the two mixed solutions, the mass ratio of indium nitrate hydrate to polyvinyl pyrrolidone is 1:0.36, the stirring time ranges from 12h to 18h, and the stirring speed ranges from 500r / min to 600r / min.
[0019] As a further limiting scheme of the preparation method of the present invention, in step 3, when the electrospinning treatment is carried out, the voltage applied to the needle is 16kV~18kV, the injection rate is 0.3ml / h~1ml / h, the collector speed is 100r / min, and the humidity is controlled at 15%rh~20%rh; in step 4, when the annealing treatment is carried out, the annealing heating rate is 5℃ / min, the maximum annealing temperature is 400℃~700℃, the annealing time is 2.5h~3.5h, and then naturally cooled to room temperature.
[0020] The present invention also provides an application of triethylamine detection of the In2O3 / MXene composite material.
[0021] Compared with the prior art, the present invention has the following beneficial effects: the In2O3 / MXene composite material disclosed in the present invention is a rod-shaped nanoparticle structure wrapped in a single-layer sheet, and there are small and dense gaps on the surface, which provide abundant active sites for the attachment of oxygen, so that a larger current response can be obtained, and the gas-sensing performance is better than that of pure indium oxide, and the detection performance of triethylamine gas is enhanced; the preparation method of the present invention is simple, the material performance is excellent, and the cost is low. In various chemical processes that require triethylamine as an industrial raw material, and systems involving the production, storage and transportation of triethylamine, the real-time detection and timely alarm of triethylamine leakage have great application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of In2O3 / MXene exemplified in the present invention;
[0023] Figure 2 This is a transmission electron microscope image of In2O3 / MXene exemplified in the present invention;
[0024] Figure 3 Element mapping diagram of In2O3 / MXene of the present invention; wherein a is a high-angle annular dark field image, b is C element, c is N element, d is O element, e is Ti element, and f is In element;
[0025] Figure 4 This is a scanning electron microscope image of the MXene exemplified in the present invention;
[0026] Figure 5 Figure a is the response-recovery curve of a pure In2O3-based sensor exposed to 1 ppm triethylamine at 1 V; Figure b is the response-recovery curve of an In2O3 / MXene-based sensor in an example of the present invention exposed to 1 ppm triethylamine at 1 V;
[0027] Figure 6The response-recovery curve of the In2O3 / MXene-based sensor of the present invention when exposed to different concentrations of triethylamine at 1V;
[0028] Figure 7 The concentration response fitting curve of the In2O3 / MXene-based sensor of the present invention when exposed to different concentrations of triethylamine at 1V;
[0029] Figure 8 The sensitivity change curve of the In2O3 / MXene-based sensor of the present invention when continuously exposed to 1 ppm triethylamine environment at 1 V;
[0030] Fig. 9 Sensitivity change curve of the In2O3 / MXene-based sensor of the present invention under different humidity environments at 1V and exposed to 1ppm triethylamine. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the embodiments.
[0032] like Figure 1 As shown, the In2O3 / MXene composite material disclosed in the present invention is a rod-shaped nanoparticle wrapped in a single layer of sheet consisting of a p-type semiconductor metal two-dimensional material MXene coated with an n-type semiconductor In2O3, and small and dense gaps are distributed on the surface of the rod-shaped nanoparticle, which is used to provide abundant active sites for the attachment of oxygen.
[0033] As a further limitation of the composite material of the present invention, the diameter of the rod-shaped nanoparticles is 30 nm to 70 nm, and the diameter of the particles is generally about 50 nm.
[0034] The present invention also provides a method for preparing an In2O3 / MXene composite material, which is used to prepare the In2O3 / MXene composite material, and the specific steps are:
[0035] Step 1, preparing a single-layer MXene sheet;
[0036] Step 2, indium nitrate hydrate (In(NO3)3·nH2O) and MXene are mixed with NN-dimethylformamide (DMF) respectively and stirred to obtain two mixed solutions, and then polyvinyl pyrrolidone (PVP) is added to the two mixed solutions and stirred again;
[0037] Step 3, electrospinning the stirred solution to obtain an In2O3 / MXene composite material precursor;
[0038] Step 4, annealing the In2O3 / MXene composite material precursor to obtain rod-shaped nanoparticles wrapped in a single layer of flakes, namely the In2O3 / MXene composite material.
[0039] As a further limitation of the preparation method of the present invention, in step 1, the specific steps for preparing a single-layer flaky MXene are:
[0040] Step 1.1, mixing hydrochloric acid (HCl) and lithium fluoride (LiF) in a polyethylene beaker, and then placing in a magnetic stirrer for heating and stirring;
[0041] Step 1.2, adding titanium aluminum carbide (Ti3AlC2) for etching, and then performing centrifugation, ultrasound and freeze-drying treatment to obtain a single-layer flaky MXene.
[0042] As a further limitation of the preparation method of the present invention, in step 1.1, the mass ratio of hydrochloric acid to lithium fluoride is 1:10 to 1:20, preferably 1:15, the reaction time of heating and stirring in the magnetic stirrer is 5 to 15 minutes, preferably 10 minutes, the stirring speed range is 300 r / min to 400 r / min, and the oil bath temperature range is 38°C to 42°C.
[0043] As a further limiting scheme of the preparation method of the present invention, in step 1.2, when aluminum titanium carbide is added, the mass ratio of aluminum titanium carbide to hydrochloric acid is 1:20 to 1:30, preferably 1:25, and the reaction time for etching ranges from 36 to 48 hours, preferably 36 hours.
[0044] As a further limitation of the preparation method of the present invention, in step 1.2, the specific steps of centrifugation, ultrasound and freeze-drying are:
[0045] First, collect the bottom precipitate, wash it 3-5 times with 1M dilute hydrochloric acid by centrifugation at a speed of 3500r / min, then wash it 3-5 times with deionized water by centrifugation at a speed of 3500r / min, until the pH is about 6, collect the precipitate and perform ultrasonication;
[0046] Then, during the ultrasonication, inert gas was introduced for protection and the mixture was placed in an ice water bath for a total of 2 h.
[0047] Finally, the upper liquid was collected and freeze-dried. The freezing time was 24 hours and the drying time was 48 hours to 60 hours.
[0048] As a further limitation of the preparation method of the present invention, in step 2, the mass ratio of indium nitrate hydrate to MXene is in the range of 10:1 to 200:1, the mass ratio of indium nitrate hydrate to NN-dimethylformamide is 1:15, the mass ratio of MXene to NN-dimethylformamide is in the range of 1:150 to 1:3000, and the stirring and mixing time with NN-dimethylformamide is 5 to 15 minutes, preferably 10 minutes.
[0049] As a further limiting scheme of the preparation method of the present invention, in step 2, after polyvinyl pyrrolidone is added to the two mixed solutions, the mass ratio of indium nitrate hydrate to polyvinyl pyrrolidone is 1:0.36, the stirring time ranges from 12h to 18h, and the stirring speed ranges from 500r / min to 600r / min.
[0050] As a further limiting scheme of the preparation method of the present invention, in step 3, when the electrospinning treatment is carried out, the voltage applied to the needle is 16kV~18kV, the injection rate is 0.3ml / h~1ml / h, the collector speed is 100r / min, and the humidity is controlled at 15%rh~20%rh; in step 4, when the annealing treatment is carried out, the annealing heating rate is 5℃ / min, the maximum annealing temperature is 400℃~700℃, the annealing time is 2.5h~3.5h, preferably 3h, and then naturally cooled to room temperature.
[0051] The present invention also provides an application of triethylamine detection of an In2O3 / MXene composite material, for example, constructing an In2O3 / MXene-based sensor for detecting triethylamine gas, and the specific construction steps are as follows:
[0052] First, the Au interdigital electrode is pretreated by polishing the Au interdigital electrode with magnesium oxide powder having a particle size of 0.4 μm and 0.02 μm, respectively. The polished electrode is first placed in anhydrous ethanol for ultrasonic cleaning for 6 to 10 minutes to remove organic dirt, and then placed in ultrapure water for ultrasonic cleaning for 10 to 15 minutes to remove residual ethanol and magnesium oxide particles, and then the electrode surface is dried with high-purity nitrogen;
[0053] Then, 3-5 mg of In2O3 / MXene composite material was weighed and mixed with 20 μm-40 μm anhydrous ethanol by ultrasonic to obtain a uniform In2O3 / MXene anhydrous ethanol composite dispersion. 3-5 μL of In2O3 / MXene anhydrous ethanol composite dispersion was transferred with a pipette and drop-casted onto the surface of the Au interdigital electrode. The electrode was modified 3-5 times in total and dried on a heating table for 2-3 hours to obtain an In2O3 / MXene-based sensor.
[0054] Then, the In2O3 / MXene-based sensor was continuously exposed to triethylamine of different concentrations to test the resistance characteristics of the sensor over time, and the test voltage was 1 V. The above preparation process and the prepared In2O3 / MXene-based sensor were tested in combination with specific examples.
[0055] Example 1
[0056] Preparation of In2O3 and construction of In2O3-based sensors:
[0057] 0.864g of indium nitrate hydrate (In(NO3)3·nH2O) was added to 15ml of NN-dimethylformamide (DMF), and the mixture was stirred evenly for 10 minutes; 2.4g of polyvinyl pyrrolidone (PVP) was added to the stirred solution and the stirring was continued for 3h; the rotation speed was 500r / min; the stirred solution was subjected to electrostatic spinning operation, and the voltage applied to the needle was 16kv; the injection rate was 1ml / h; the collector speed was 100r / min; the humidity was controlled at 15%rh~20%rh; the spinning material was subjected to high temperature annealing operation, and the annealing heating rate was 5℃ / min; the maximum annealing temperature was 400℃, the annealing time was 3h, and the temperature was naturally cooled to room temperature to obtain pure In2O3.
[0058] The Au interdigital electrode is polished with magnesium oxide powder with particle sizes of 0.4 μm and 0.02 μm respectively, and the polished electrode is first placed in anhydrous ethanol for ultrasonic cleaning for 6 to 10 minutes to remove organic dirt; then placed in ultrapure water for ultrasonic cleaning for 10 to 15 minutes to remove residual ethanol and magnesium oxide particles, and then the electrode surface is dried with high-purity nitrogen; 3 to 5 mg of pure In2O3 is weighed, and it is ultrasonically mixed with 20 μm to 40 μm anhydrous ethanol to obtain a uniform In2O3 anhydrous ethanol composite dispersion, and 3 to 5 μL of the In2O3 anhydrous ethanol composite dispersion is transferred with a pipette and drop-casted onto the surface of the Au interdigital electrode, which is modified 3 to 5 times in total, and heated and dried on a heating table for 2 to 3 hours to obtain an In2O3-based sensor.
[0059] Example 2
[0060] Preparation of In2O3 / MXene composites and construction of In2O3 / MXene-based sensors:
[0061] First, 20 ml of HCl and 1.6 g of LiF were mixed and added to a beaker for 10 min. 1 g of Ti3AlC2 was added to the mixed liquid and placed in an oil bath magnetic stirring pot for 36 h. The speed was 400 r / min. The oil bath temperature was 38°C to 42°C. The resulting solution was centrifuged, ultrasonicated, and freeze-dried for 60 h to obtain a single-layer flaky MXene.
[0062] Then, 0.864 g of indium nitrate hydrate (In(NO3)3·nH2O) and 0.864 mg of MXene were mixed with 7.5 ml of NN-dimethylformamide (DMF) and stirred evenly, and then 2.4 g of polyvinyl pyrrolidone (PVP) was added and stirred for 12 hours; the stirred solution was electrospun, and the voltage applied to the needle during the electrospinning operation was 16 kV; the injection rate was 0.3 ml / h; the collector speed was 100 r / min; the humidity was controlled at 15% rh~20% rh to obtain an In2O3 / MXene composite material precursor; the obtained material was subjected to high-temperature annealing treatment, and the annealing heating rate was 5°C / min; the annealing temperature was 400°C, the annealing time was 3 hours, and the temperature was naturally cooled to room temperature to obtain an In2O3 / MXene composite material.
[0063] from Figure 1 and Figure 2 It can be seen that the In2O3 / MXene composite material is a rod-shaped nanoparticle wrapped in a single layer of flakes, and the diameter of the rod-shaped nanoparticle is about 50nm. In addition, there are small and dense gaps on the surface of the rod-shaped nanoparticle structure wrapped in a single layer of flakes, which also provides abundant active sites for the attachment of oxygen, thereby obtaining a larger current response, having better gas-sensing performance than pure indium oxide, and enhancing the detection performance of triethylamine gas. Figure 3 This is the element mapping diagram of In2O3 / MXene composite material, such as Figure 3 As shown, In and O elements belong to In2O3, and C, N and Ti elements belong to MXene. Figure 3 It can be seen that the In element and the O element are evenly dispersed on the wrapped rod-shaped particles, which strongly confirms the successful synthesis of In2O3. It can also be seen that MXene is evenly loaded on the surface of In2O3 particles, thus proving that the present invention successfully prepared the In2O3 / MXene composite material.
[0064] Figure 4 This is the SEM image of MXene. It can be seen that a single-layer flaky MXene was successfully prepared, laying the foundation for the successful loading of pure materials.
[0065] The Au interdigital electrode was polished with alumina powder with particle sizes of 0.4 μm and 0.02 μm, respectively. The polished electrode was first placed in anhydrous ethanol for ultrasonic cleaning for 6 to 10 minutes to remove organic dirt; then placed in ultrapure water for ultrasonic cleaning for 10 to 15 minutes to remove residual ethanol and magnesium oxide particles, and then the electrode surface was dried with high-purity nitrogen; 3 to 5 mg of In2O3 / MXene composite material was weighed, and it was ultrasonically mixed with 20 μm to 40 μm anhydrous ethanol to obtain a uniform In2O3 / MXene anhydrous ethanol composite dispersion, and 3 to 5 μL of the In2O3 / MXene anhydrous ethanol composite dispersion was transferred with a pipette and drop-casted onto the surface of the Au interdigital electrode, modified 3 to 5 times in total, and heated and dried on a heating table for 2 to 3 hours to obtain an In2O3 / MXene-based sensor.
[0066] Example 3
[0067] The In2O3-based sensor and In2O3 / MXene-based sensor obtained according to the method of Example 1 and Example 2 were exposed to 1 ppm triethylamine, with a loading voltage of 1 V, and the change curve of the sensor resistance over time was tested. Figure 5 As shown, it can be seen that the response time of the In2O3-based sensor is 120s and the recovery time is 219s, while the response time of the In2O3 / MXene-based sensor is 1s and the recovery time is 11s. Compared with pure In2O3, the response and recovery time are greatly shortened, showing the excellent triethylamine sensing performance of the composite material.
[0068] Example 4
[0069] The In2O3 / MXene-based sensor obtained according to the method of Example 2 was continuously exposed to different triethylamine concentration environments to test the change curve of the sensor resistance over time. The change of resistance over time is shown in Figure 6 and 7 As shown, the results show that as the concentration of triethylamine gradually increases, the resistance value of the material gradually decreases, exhibiting the gas sensing behavior of an N-type semiconductor.
[0070] From the above, it can be seen that the In2O3 / MXene-based sensor prepared by the present invention has sensitive detection of triethylamine and short response recovery time, and has excellent performance in the detection of triethylamine. Therefore, it has great application potential in various chemical processes that require triethylamine as an industrial raw material, and in systems involving the production, storage and transportation of triethylamine, real-time detection and timely alarm of triethylamine leakage.
[0071] Example 5
[0072] The In2O3 / MXene-based sensor obtained according to the method of Example 2 was placed in a 1ppm concentration triethylamine environment for a long time, and the change curve of the sensor resistance over time was tested every seven days. The long-term stability of the In2O3 / MXene-based sensor for triethylamine detection was evaluated by detecting the change of resistance over time. The change of sensitivity over time is shown in Figure 2. Figure 8 As shown, Figure 8 The results show that the sensitivity of the material has not changed much over a month, proving that the material has good long-term stability. Then, the sensor's response to triethylamine was tested by changing the ambient humidity. Fig. 9 As shown in the figure, the response value of the material does not change much when the ambient humidity changes, which proves that the material has excellent moisture resistance.
[0073] From the above, it can be seen that the In2O3 / MXene-based sensor synthesized in the present invention is sensitive to the detection of triethylamine and has a short response recovery time, and has excellent performance in the detection of triethylamine. Therefore, it has great application potential in various chemical processes that require triethylamine as an industrial raw material, and in systems involving the production, storage and transportation of triethylamine, for real-time detection and timely alarm of triethylamine leakage.
[0074] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.
Claims
1. An In2O3 / MXene composite material, characterized in that: The rod-shaped nanoparticles are wrapped in a single layer of sheets consisting of p-type semiconductor metal two-dimensional material MXene coated with n-type semiconductor In2O3, and there are gaps distributed on the surface of the rod-shaped nanoparticles to provide abundant active sites for the attachment of oxygen.
2. The In2O3 / MXene composite material according to claim 1, characterized in that: The diameter of the rod-shaped nanoparticles is 30nm to 70nm.
3. A method for preparing an In2O3 / MXene composite material, characterized in that: For preparing the In2O3 / MXene composite material according to claim 1 or 2, the specific steps are: Step 1, preparing a single-layer MXene sheet; Step 2, indium nitrate hydrate and MXene are mixed with NN-dimethylformamide respectively, and then stirred to obtain two mixed solutions, and then polyvinyl pyrrolidone is added to the two mixed solutions, and then stirred to mix; Step 3, subjecting the stirred and mixed solution to electrospinning to obtain an In2O3 / MXene composite material precursor; Step 4, annealing the In2O3 / MXene composite material precursor to obtain rod-shaped nanoparticles wrapped in a single layer of flakes, namely the In2O3 / MXene composite material.
4. The method for preparing the In2O3 / MXene composite material according to claim 3, characterized in that: In step 1, the specific steps for preparing a single-layer MXene are: Step 1.1, mixing hydrochloric acid and lithium fluoride in a polyethylene beaker, and then heating and stirring in a magnetic stirrer; Step 1.2, adding aluminum titanium carbide for etching, and then performing centrifugation, ultrasound and freeze-drying treatment to obtain a single-layer flaky MXene.
5. The method for preparing the In2O3 / MXene composite material according to claim 4, characterized in that: In step 1.1, the mass ratio of hydrochloric acid to lithium fluoride is 1:10 to 1:20, the reaction time of heating and stirring in the magnetic stirrer is 5 to 15 minutes, the stirring speed range is 300 r / min to 400 r / min, and the oil bath temperature range is 38°C to 42°C.
6. The method for preparing the In2O3 / MXene composite material according to claim 4, characterized in that: In step 1.2, when aluminum titanium carbide is added, the mass ratio of aluminum titanium carbide to hydrochloric acid is 1:20 to 1:30, and the etching reaction time ranges from 36 to 48 hours.
7. The method for preparing the In2O3 / MXene composite material according to claim 3, characterized in that: In step 2, the mass ratio of indium nitrate hydrate to MXene is in the range of 10:1 to 200:1, the mass ratio of indium nitrate hydrate to NN-dimethylformamide is 1:15, the mass ratio of MXene to NN-dimethylformamide is in the range of 1:150 to 1:3000, and the stirring and mixing time with NN-dimethylformamide is 5 to 15 minutes.
8. The method for preparing the In2O3 / MXene composite material according to claim 3, characterized in that: In step 2, after polyvinyl pyrrolidone is added to the two mixed solutions, the mass ratio of indium nitrate hydrate to polyvinyl pyrrolidone is 1:0.36, the stirring time ranges from 12h to 18h, and the stirring speed ranges from 500r / min to 600r / min.
9. The method for preparing the In2O3 / MXene composite material according to claim 3, characterized in that: In step 3, during the electrospinning treatment, the voltage applied to the needle is 16kV~18kV, the injection rate is 0.3ml / h~1ml / h, the collector speed is 100r / min, and the humidity is controlled at 15%rh~20%rh; in step 4, during the annealing treatment, the annealing heating rate is 5℃ / min, the maximum annealing temperature is 400℃~700℃, the annealing time is 2.5h~3.5h, and then naturally cooled to room temperature.
10. An application of triethylamine detection of the In2O3 / MXene composite material according to claim 1 or 2.
Citation Information
Patent Citations
Preparation method of In2O3 nanoparticles / MoO3 nanorod composite materials
CN105540670A
One-dimensional indium oxide hollow nanotube / two-dimensional zinc ferrite nanosheet heterojunction composite material and application thereof in removal of pollutants in water
CN110180548A
Synthesis method of In2O3 / ZnO micro-flower structure assembled by conical rods
CN111661871A
WO3 / MXene nano-composite film, wireless NFC (near field communication) trimethylamine sensor and preparation method and application of WO3 / MXene nano-composite film
CN115266842A
Composite material with specific selectivity on triethylamine in mixed gas, preparation method of composite material and application of composite material in environment detection
CN116297708A